BIM Digital Shadow Technology and Risk Assessment Method of the Deep Foundation Pit’s Behavior for Zibo Light Rail - Yuan, Minghui; Yuan, Changfeng; Chen, Fu; Li, Liang; Hong, Yong; Yu, Guangming; Lei, Jun (Frontiers in Earth Science, 2022)
With the shortage of land resources, there has been a trend toward increasingly deep foundation pit engineering in urban areas. It is extremely important to reflect on the behavior and safety of deep foundation pits and conduct risk assessments in time. A nonhomologous and multi-indicator deep foundation pit risk assessment model was studied for nine types of nonhomologous on-site data monitored in the deep foundation pit. Based on the BIM (Building Information Modeling) technology, a family of monitored points was created that reflects the information on site from a deep foundation pit. The data visualization module was redeveloped by using Visual Studio 2019 to map the on-site data monitored to the components in the BIM model, which can visualize the data monitored in the BIM model of deep foundation pits. On this basis, the assessment of the safety level of deep foundation pits was realized in combination with a risk assessment model. Through the instance of the deep foundation pit of Zibo light rail, the analysis shows that the new visualization and risk assessment method can help construction workers locate dangerous units and formulate corresponding prevention and control measures better and faster.